The impact of COVID-19 school disruptions on children’s learning - Blackwell, Courtney K.; Mansolf, Maxwell; Deoni, Sean C. L.; Ganiban, Jody M.; Leve, Leslie D.; Margolis, Amy E.; McGrath, Monica; Nozadi, Sara S.; O’Shea, T. Michael; Sherlock, Phillip; Zhao, Qi; LeWinn, Kaja Z.; et al. (Frontiers in Education, 2024)
National health policies to stop the spread of the COVID-19 virus in the US resulted in widespread school closures and disrupted learning in Spring 2020. This study draws on unique individual-level data from n = 282 5-12-year-olds enrolled in the NIH Environmental influences on Child Health Outcomes (ECHO) Research Program to investigate associations between caregiver-reported duration of Spring 2020 learning disruptions and academic achievement. Linear regression analyses estimated that children who experienced more than four weeks of instruction disruptions in Spring 2020 scored 4.5 points [95% CI: -8.77, -.22] lower on age-normed math assessments compared to peers who had four or fewer weeks of disruption, adjusting for sociodemographic variables, prepandemic vocabulary, and COVID-19 family hardships and stress. No differences were found for reading. Children whose caregivers had higher levels of pandemic-related traumatic stress and lower educational attainment also had lower math scores, adjusting for all other covariates. Results suggest educators and schools focus additional attention on supporting math instruction for children who experienced extended learning disruptions.